2018
DOI: 10.1152/ajpheart.00714.2017
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA’s journey to the center of the mitochondria

Abstract: MicroRNAs (miRNAs) are known as the master regulators of gene expression, and for the last two decades our knowledge of their functional reach keeps expanding. Recent studies have shown that a miRNA's role in regulation extends to extracellular and intracellular organelles. Several studies have shown a role for miRNA in regulating the mitochondrial genome in normal and disease conditions. Mitochondrial dysfunction occurs in many human pathologies, such as cardiovascular disease, diabetes, cancer, and neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 115 publications
0
53
0
2
Order By: Relevance
“…However, further studies are required to examine the extent to which pre‐miRs also undergo processing within the mitochondria. Potential transport mechanisms of mature and immature miRNAs into the mitochondria are discussed in other reviews (Bandiera et al., ; Borralho, Rodrigues, & Steer, ; Duarte, Palmeira, & Rolo, ; Macgregor‐Das & Das, ; Sripada, Tomar & Singh, ) and suggest a role for AGO2 (Maniataki & Mourelatos, ), polynucleotide phosphorylase (PNPASE; Shepherd et al., ; G. Wang et al., ), P‐bodies (Huang et al., ) and voltage‐gated ion channels (Salinas et al., ).…”
Section: Immature Forms Of Mirna and Mirna‐associated Proteins Are Exmentioning
confidence: 97%
See 1 more Smart Citation
“…However, further studies are required to examine the extent to which pre‐miRs also undergo processing within the mitochondria. Potential transport mechanisms of mature and immature miRNAs into the mitochondria are discussed in other reviews (Bandiera et al., ; Borralho, Rodrigues, & Steer, ; Duarte, Palmeira, & Rolo, ; Macgregor‐Das & Das, ; Sripada, Tomar & Singh, ) and suggest a role for AGO2 (Maniataki & Mourelatos, ), polynucleotide phosphorylase (PNPASE; Shepherd et al., ; G. Wang et al., ), P‐bodies (Huang et al., ) and voltage‐gated ion channels (Salinas et al., ).…”
Section: Immature Forms Of Mirna and Mirna‐associated Proteins Are Exmentioning
confidence: 97%
“…transport mechanisms of mature and immature miRNAs into the mitochondria are discussed in other reviews(Bandiera et al, 2013;Borralho, Rodrigues, & Steer, 2015;Duarte, Palmeira, & Rolo, 2014;Macgregor-Das & Das, 2018; and suggest a role for AGO2(Maniataki & Mourelatos, 2005), polynucleotide phosphorylase (PNPASE;Shepherd et al, 2017;G. Wang et al, 2010), P-bodies(Huang et al, 2011) and voltage-gated ion channels(Salinas et al, 2006).The presence of AGO2 and dicer in the mitochondria, along with immature forms of miRNAs, reinforces the idea that some level of miRNA-mediated post-transcriptional regulation occurs in TA B L E 1 Skeletal muscle-related mitochondrial microRNAs mitochondrial miRNAs were classified as canonical myomiRs, skeletal muscle-enriched miRNAs and cardiac muscle-enriched miRNAs.…”
mentioning
confidence: 99%
“…In proliferating cells, genes with shorter 3′‐UTR can omit their miRNA target sites, resulting in higher protein expression. Finally, miRNAs can be sequestered by mRNAs, lncRNAs, and circRNAs that contain miRNA binding sites and thus acting as a sponge . Argonaute (Ago) protein is an RNA‐binding protein, which exists in the extracellular space as a free protein or in secreted exosomes along with other RNA‐processing proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, miRNAs can be sequestered by mRNAs, lncRNAs, and circRNAs that contain miRNA binding sites and thus acting as a sponge. [65][66][67][68] Argonaute (Ago) protein is an RNAbinding protein, which exists in the extracellular space as a free protein or in secreted exosomes along with other RNAprocessing proteins. Ago accumulates in cytoplasmic processing bodies (P-bodies), where additional binding interactions promote mRNA decay and translational inhibition.…”
mentioning
confidence: 99%
“…The subset of miRNAs, which translocate into the mitochondria and are functionally active, i.e., RNA-induced silencing complex, or RISC, is inside the mitochondrial compartment, are termed mitochondrial miRNA or MitomiR. The mitochondrial miRNA translocation phenomenon has not been extensively studied (Macgregor-Das and Das, 2018 ), but MitomiRs can influence various mitochondrial functions, such as the TCA, ETC, lipid metabolism, and amino acid metabolism (Baradan et al, 2017 ). It has been demonstrated that MitomiRs can post-translationally regulate gene function inside the mitochondrial fraction either by targeting a nuclear-encoded gene present in the mitochondria or by targeting a mitochondrial encoded-gene (Das et al, 2012 , 2014 , 2017 ).…”
Section: Introduction To Mitochondrial Micrornasmentioning
confidence: 99%